1973
DOI: 10.1111/j.1460-2466.1973.tb00960.x
|View full text |Cite
|
Sign up to set email alerts
|

Experiments in Televised Violence and Verbal Aggression: Two Exploratory Studies1

Abstract: Within the scarce literature concerning verbal aggression, there is some indication that verbal and physical aggression may have similar inhibitions conditioned t o each. T w o experiments were carried out to explore this possible relationship. In the first, middle and lower socioeconomic status ( S E S ) adolescent boys were exposed to televised physical aggression with and without consequences to the victim shown. In the second experiment, middle and lower S E S adolescent boys were exposed to televised ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…As noted earlier, research has shown that the depiction of a victim's harm and pain can inhibit the learning of aggression among viewers (Baron, 1971a;1971b;Wotring & Greenberg, 1973). Yet, across several measures, children's shows are less likely than other types of programming to portray the serious consequences of violence.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…As noted earlier, research has shown that the depiction of a victim's harm and pain can inhibit the learning of aggression among viewers (Baron, 1971a;1971b;Wotring & Greenberg, 1973). Yet, across several measures, children's shows are less likely than other types of programming to portray the serious consequences of violence.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, violence that goes unpunished can elevate fear, particularly when it appears to be unjust or random (Bryant et al, 1981). Seventh, the consequences of violence for the victim are important contextual cues; the explicit depiction of a victim's physical harm and pain can decrease or inhibit the learning of aggression among viewers (Baron 1971a(Baron , 1971bWotring & Greenberg, 1973). Finally, violence that is portrayed as humorous may contribute to aggression (Baron, 1978;Berkowitz, 1970), and also may desensitize viewers to the seriousness of such behaviors (Jablonski & Zillmann, 1995), though this particular contextual factor has received the least empirical investigation.…”
Section: The National Television Violence Study (Ntvs)mentioning
confidence: 97%
“…Seventh-, eighth-, and ninth-grade boys did not become more verbally aggressive after exposure to televised verbal aggression (Wotring & Greenberg, 1973). It is doubtful that children under the age of 12 understand sexual language and innuendo; therefore it is unlikely that vulgarities have any negative effects (Donnerstein, Wilson, & Linz, 1992;Jay, 1992).…”
Section: Effects Of Verbal Vulgarities On Childrenmentioning
confidence: 97%
“…For example, exposure to violent media has been associated with beliefs about others' hostility (Carver, Ganellen, Froming, & Chambers, 1983) a willingness to use violence to solve problems (Dominick & Greenberg, 1972), increased verbal aggression in young boys (Wotring & Greenberg, 1973), and immediate (Berkowitz, 1965) as well as delayed (Zillmann & Weaver, 1999) acts of hostility.…”
Section: Vr Violent Video Games Telepresence and Hostilitymentioning
confidence: 98%